Financial and Economic Issues in Emerging Markets 2022
DOI: 10.58830/ozgur.pub1.c40
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Renewable Energy Consumption and Economic Growth in Selected Developed and Developing Economies

Abstract: Bu kitabın Türkiye'deki her türlü yayın hakkı Özgür Yayınları Tic. Ltd. Şti'ne aittir, tüm hakları saklıdır. Kitabın tamamı veya bir kısmı 5846 sayılı yasanın hükümlerine göre, kitabı yayınlayan firmanın ve yazarlarının önceden izni olmadan elektronik, mekanik, fotokopi ya da herhangi bir kayıt sistemiyle çoğaltılamaz, yayınlanamaz, depolanamaz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This indicates that an increase in energy consumption will increase the volume of carbon dioxide emissions, parallel to the findings of Wang et al, (2013), Mohiuddin et al, (2016), Asumadu-Sarkodie and Owusu (2017). Taking into account the fact that energy consumption is one of the main contributors to environmental pollution affecting air quality, Cetin et al, (2015), Cheema and Javid (2015), Shahzad et al, (2015), Li et al, (2016), Sinha et al, (2017) suggested making a stern environmental and energy policy, and recommended the government to implement new procedures to transfer renewable energy consumption in the industrial sector. Note that countries should be focused on the long-term benefits of renewable energy at least to achieve the goal of restricting GHG emissions up to 2030.…”
Section: Resultsmentioning
confidence: 55%
“…This indicates that an increase in energy consumption will increase the volume of carbon dioxide emissions, parallel to the findings of Wang et al, (2013), Mohiuddin et al, (2016), Asumadu-Sarkodie and Owusu (2017). Taking into account the fact that energy consumption is one of the main contributors to environmental pollution affecting air quality, Cetin et al, (2015), Cheema and Javid (2015), Shahzad et al, (2015), Li et al, (2016), Sinha et al, (2017) suggested making a stern environmental and energy policy, and recommended the government to implement new procedures to transfer renewable energy consumption in the industrial sector. Note that countries should be focused on the long-term benefits of renewable energy at least to achieve the goal of restricting GHG emissions up to 2030.…”
Section: Resultsmentioning
confidence: 55%